Abnormal Newborn Screen in an Ex-premature Infant fed Goat Milk - Simon, Trishell; Belnavis, Gillian; Reynolds, Kimberly (International Journal of Contemporary Pediatrics, 2021)
Newborn screening is an important tool in the early diagnosis or detection of rare genetic and metabolic conditions. There are external factors that may influence results. One such is infant nutrition. This article discusses the case of a three month old infant with an abnormal newborn screen in the setting of being fed whole goat milk as well as the importance of reviewing infant nutrition with parents.